Means End Analysis (MEA): A Learning Model to Improve Mathematics Cognitive Learning Outcomes in the Post-Pandemic COVID-19 - Salahudin, Anas; Iqlima Mufida, Salwa; Marthyane Pratiwi, Inne (KnE Social Sciences, 2024)
This research is motivated by the low cognitive learning outcomes of students in solving math problems. Alternative learning to the low cognitive learning outcomes of students is to apply the Means-End Analysis learning model. This model is designed using a quasi-experimental method. This study aims to determine the difference in the average cognitive learning outcomes of class VI students in learning mathematics using the Means-End Analysis model with conventional learning using the Direct Instruction model. The population of this research is all sixth-grade students of SDN 267 Bandung for the academic year 2021/2022. The samples taken were class VI A, and class VI B using a purpose sampling technique. Data collection techniques used are tests and observations. The data analysis technique used an independent t-test with a significance level of 5%. The results obtained that: there is a difference in the average cognitive learning outcomes of students between those taught with the Means End Analysis learning model and conventional learning using the Direct Instruction model. So that the Means-End Analysis model can be used as a learning model that can improve cognitive mathematics learning outcomes in the post-pandemic COVID-19. Keywords: mathematics cognitive learning outcomes, means end analysis (MEA): a learning model, post-pandemic covid-19